Indocyanine Green Fluorescence Imaging-Guided Surgery in Primary and Metastatic Liver Tumors. (February 2018) - Lieto, Eva; Galizia, Gennaro; Cardella, Francesca; Mabilia, Andrea; Basile, Nicoletta; Castellano, Paolo; Orditura, Michele; Auricchio, Annamaria
Background . After surgery for liver tumors, recurrence rates remain high because of residual positive margins or undiagnosed lesions. It has been suggested that detection of hepatic tumors can be obtained with near-infrared fluorescence imaging (FI). Indocyanine green (ICG) has been used with contrasting results. The aims of this study were to explore ICG-FI-guided surgery methodology and to assess its potential applications. Materials and Methods . Out of 14 patients with liver tumors, 5 were not operated on, and 9 patients (3 primary and 6 metastatic tumors) underwent surgery. ICG (0.5 mg/kg) was injected intravenously 24 hours before surgery. Fluorescence was investigated prior to resection to detect liver lesions, during hepatic transection to guide surgery, on both cross-section and benchtop to assess surgical margins, and for pathological evaluation. Results . All operations were successful and had a short duration. ICG-FI detected all already known lesions (n = 10), and identified 2 additional small tumors (1 hepatocarcinoma and 1 metastasis, diagnostic improvement = 20%). Two hepatocarcinomas were hyperfluorescent; the remaining one, with a central hypofluorescent area and a hyperfluorescent ring, was indeed a mixed cholangiohepatocarcinoma. All metastatic nodules were hypofluorescent with a hyperfluorescent rim. In all cases, in vivo and ex vivo fluorescence revealed clear liver margins. Postoperative pathological examination greatly benefited of liver fluorescence to assess radicality. Conclusion . ICG-FI-guided surgery was shown to be an effective tool to improve both intraoperative staging and radicality in the surgical treatment of primary and metastatic liver tumors.